The Effect of the Number of Baffles on the Performance of Solar Updraft Tower: A Numerical Study - Ariwibowo, Teguh Hady; Safitra, Arrad Ghani; Ismah, Paradya Nabilah; Hidayatullah, Muhammad Muslih; Amelia, Firyal Nisa (JRST (Jurnal Riset Sains dan Teknologi), 2024)
Enhancing the amount of flow field and heat transfer characteristic is an effective way to increase the performance of SUT plants. The velocity magnitude and heat transfer characteristic can be increased by adding passive flow control in the form of baffles. This study investigated the SUT prototype's flow field and heat transfer characteristics numerically using one, two, and three baffle variations through 2D axisymmetric analysis with the standard k-epsilon turbulence model using a Computational Fluid Dynamics (CFD) method. The results of the CFD solution obtained profiles of temperature distribution, velocity, streamline, kinetic power, and turbulent kinetic energy of each baffle variation. SUT with two-baffle variation is superior to the others by having a maximum air velocity of 6.248 m/s and increasing SUT performance by 104.769 %, while the three-baffle variation has the highest temperature profile and the most circulating flow effect with an increase in SUT performance of 51.524%. As the number of baffles in the SUT increases, the pressure drop also increases, but the effect of the pressure drop is not significant.